Peningkatan Hasil Belajar Siswa tentang Gerak Lurus dengan Menerapkan Model NHT di Kelas X MIPA 1 SMAN 2 Solok - Susanti, Rosi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2022)
This research aims to increase the student’s learning achievement about straight movement by applying NHT model at grade X of natural. Science class I Physics is one of the subjects that is not interesting to some of the student of SMAN 2 Solok. Because it is considered as a difficult subject, so that they tend to be passive to join the physics class. One of the models to increase the student activeness is NHT model. This research is an action research by having collaboration between the researcher and the researcher and the physics teacher. The subject research are 36 student of SMAN 2 Solok,grade X of natural science class I In year of 2021/2022. The technique of data collection uses student’s activities observation space and student’s test marks. The result show that by applying NHT model at the material of straight movement at grade x of natural science I at SMA 2 Solok. There is increase to: (1). The student’s activities at cycle I that is 72,9%, then at the cycle 2 it become 95 %, the percentage increasing is 22,9%.(2).Teacher’s activeness at the first meeting is 73,07% and getting increases to the forth meeting to 90,74%. It increases 17,67% with the very good predicate, and (3).The student learning achievement, at the cycle 2 there are 5 students (14%) got very good score, 25 students(69,5%) got good score, 5 students(14%) got middle score, and there is only I student(24,77 %) got the lowest score.